Combining Multi-Canal Vestibular Implant Stimulation to Restore the Vestibulo-Ocular Reflex in 3D - Stan C. J. van Boxel; Bernd L. Vermorken; Benjamin Volpe; Nils Guinand; Angelica Perez-Fornos; Elke M. J. Devocht; Raymond van de Berg (IEEE Transactions on Neural Systems and Rehabilitation Engineering, 2025)
Introduction: Vestibular implants targeting the semi-circular canals might offer a potential treatment approach for vestibulopathy patients. Electrical stimulation is provided to all three canals to restore gaze stabilization in all three planes of space. This study evaluated the effect of electrically stimulating multiple canals at the same time. It was hypothesized that eye responses of single-canal stimulation could predict eye responses of multi-canal stimulation, using vector summation. This might provide valuable information for future vestibular implant fitting strategies. Methods: Nine subjects with an investigational vestibulo-cochlear implant participated in an experiment evaluating the vestibulo-ocular reflex in response to single and multi-canal electrical stimulations. Single-canal responses were combined by vector summation to predict the multi-canal response. The prediction was compared with measured multi-canal responses. The responses were evaluated based on peak eye velocity and alignment. Results: Eye responses to multi-canal vestibular stimulation did not consistently correspond to the sum of single-canal responses. Subsets of predictions appeared within the expected range of variation, while other subsets demonstrated over- or underestimation. Conclusion: Eye responses to combined multi-canal stimulation cannot be accurately predicted by summation of single-canal responses. These findings suggest that vestibular implant fitting should not rely exclusively on single-canal measurements. Instead, advanced fitting strategies that account for multi-canal interactions are likely necessary to optimize outcomes.